Curriculum Harmonization in the Pedagogical Framework of UIN K.H. Abdurrahman Wahid Pekalongan - Mohammad Syaifuddin; Salafudin Salafudin; Arditya Prayogi; Norma Alias (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
The effectiveness of a curriculum depends on its alignment with a coherent scientific philosophy that reflects real conditions. This study examines the application of the philosophy of scientific harmonization in the curriculum structure of K.H. Abdurrahman Wahid State Islamic University (UIN) Pekalongan. Using a qualitative field research approach, data were collected from university leadership, lecturers, and the institutional transition team, alongside supporting documentation. Analysis employed an interactive model of data reduction, presentation, and verification. Findings indicate that UIN Pekalongan deliberately adopted the philosophy of scientific harmonization to overcome the dichotomy between religious and general sciences. This approach avoids both extreme theocentric and anthropocentric orientations, promoting instead a balanced integration framed as the “Arc of Scientific Harmonization” or “Scientific Orchestra,” with Tauhid serving as its unifying foundation. The curriculum structure reflects this principle by allocating 44% of credits to general sciences and 36% to religious sciences, achieving an overall integration rate of 17%. While this model successfully balances religious and general knowledge, a significant limitation is the minimal inclusion of technology-related courses, which account for only 3% of the curriculum. This gap poses challenges for institutional competitiveness in the context of the Fourth Industrial Revolution. The study concludes that UIN Pekalongan has made important strides in implementing a harmonized curriculum model, yet greater emphasis on technological content is needed to ensure its sustainability and relevance in the digital era.